Functionally different PIN proteins control auxin flux during bulbil development in Agave tequilana - Abraham Juarez, Maria Jazmin; Hernandez Cardenas, Rocio; Santoyo Villa, Jose Natzul; O'Connor, Devin; Sluis, Aaron; Hake, Sarah; Ordaz-Ortiz, José Juan; Terry, Leon A.; Simpson, June (Oxford University Press (OUP), 2015)
In Agave tequilana, reproductive failure or inadequate flower development stimulates the formation of vegetative bulbils at the bracteoles, ensuring survival in a hostile environment. Little is known about the signals that trigger this probably unique phenomenon in agave species. Here we report that auxin plays a central role in bulbil development and show that the localization of PIN1-related proteins is consistent with altered auxin transport during this process. Analysis of agave transcriptome data led to the identification of the A. tequilana orthologue of PIN1 (denoted AtqPIN1) and a second closely related gene from a distinct clade reported as ‘Sister of PIN1’ (denoted AtqSoPIN1). Quantitative real-time reverse transcription–PCR (RT-qPCR) analysis showed different patterns of expression for each gene during bulbil formation, and heterologous expression of the A. tequilana PIN1 and SoPIN1 genes in Arabidopsis thaliana confirmed functional differences between these genes. Although no free auxin was detected in induced pedicel samples, changes in the levels of auxin precursors were observed. Taken as a whole, the data support the model that AtqPIN1 and AtqSoPIN1 have co-ordinated but distinct functions in relation to auxin transport during the initial stages of bulbil formation.
Keywords: agave tequilana; auxin flux; bulbil; development; gene expression; immunolocalization; PIN proteins